Os impactos dos Mecanismos Fiscais no Financiamento do Sistema Único de Saúde - Muller, Barbara Kaiser (2022)
Considering the process of dismantling Social Security Policies and, consequently, the Unified Health System, the present work aims to analyze two fiscal mechanisms that present themselves as major obstacles to the financial support of the system: 1) The Untying of Federal Revenue, in progress in the country since 1994, which reallocates resources destined to the Social Security budget for the purpose of paying off the external debt and generating a primary surplus; and, 2) Following the same economic logic guided by financialized capital, in 2016 the Constitutional Amendment to the Public Expenditure Ceiling, which regulated the “freeze” of public spending for the next 20 years, which will have disastrous consequences in the provision of public services. Finally, considering the emergency of the New Coronavirus Pandemic (COVID-19), the work will seek to analyze whether there was flexibility in such measures. Through document analysis and literature review (secondary data) it was noticed that both measures are aligned with the premise of a minimal State, reducing public spending that seeks to guarantee the accumulation and legitimation of Capital, contrary to the interest of defending the social rights affirmed in the Federal Constitution of 1988.